Cloning and Characterization of the Bile Salt Hydrolase Genes (bsh) from Bifidobacterium bifidum Strains - Kim, Geun-Bae (American Society for Microbiology, 2004)
Biochemical characterization of the purified bile salt hydrolase (BSH) from Bifidobacterium bifidum ATCC 11863 revealed some distinct characteristics not observed in other species of Bifidobacterium. The bsh gene was cloned from B. bifidum, and the DNA flanking the bsh gene was sequenced. Comparison of the deduced amino acid sequence of the cloned gene with previously known sequences revealed high homology with BSH enzymes from several microorganisms and penicillin V amidase (PVA) of Bacillus sphaericus. The proposed active sites of PVA were highly conserved, including that of the Cys-1 residue. The importance of the SH group in the N-terminal cysteine was confirmed by substitution of Cys with chemically and structurally similar residues, Ser or Thr, both of which resulted in an inactive enzyme. The transcriptional start point of the bsh gene has been determined by primer extension analysis. Unlike Bifidobacterium longum bsh, B. bifidum bsh was transcribed as a monocistronic unit, which was confirmed by Northern blot analysis. PCR amplification with the type-specific primer set revealed the high level of sequence homology in their bsh genes within the species of B. bifidum.